False-Bird-of-Paradise – A Striking Bloom - Malakar, Moumita (Indian Horticulture, 2021)
Flowers are an integral part of human life due to their diversity in beauty, form, texture, colour and fragrance. Production and consumption of tropical flowers are increasing in many countries around the world since they’re perceived by many flower consumers as exotic and unusual, with a potential market in temperate countries. In this backdrop ‘False-Bird-of-Paradise’ also admired as Lobster’s claw, Parrots flower, Parrot plantain, False plantain, etc. (botanically recognized as Heliconia species) is gaining popularity in Indian market counting West-Bengal as an emerging flower crop.